A new species of Bulbophyllum (Orchidaceae; Epidendroideae) from Papua New Guinea - Thoerle, Lisa; Phillips, William A. (Phytotaxa, 2019)
Bulbophyllum rinkei, a new species in Bulbophyllum sect. Monanthaparva from Papua New Guinea, is described and illustrated. Bulbophyllum rinkei is distinguished from the similar B. pterostele by its flowers with a trilobed lip with large, rounded, erect basal lateral lobes (vs. oblong with erect lateral margins) and a column with deltoid stelidia with an obtuse triangular tooth on the upper margin (vs. spatulate, truncate).